Green Health - Marcel Cardinali (A+BE: Architecture and the Built Environment)
This doctoral research explores if and how green spaces are able to mitigate the global disease burden of non-communicable diseases (NCDs), by examining the role of green space characteristics and their proximity for three key theorized pathways: (1) The inviting character of green spaces to be more physically active and their health benefits; (2) the ability of green spaces to promote social cohesion and in turn mental health; (3) and the mitigation potential of green spaces to reduce air pollution and their associated health benefits. However, inconsistencies in research methodologies, definitions, and design hamper the synthesis of findings in the green space health research domain. This dissertation aims to bridge these gaps by developing a theoretical and methodological framework examining the proximity to and key characteristics of green spaces, focusing on their role in physical activity, social cohesion, and air pollution health pathways. The main research question is: How do proximity to and characteristics of green spaces affect pathways to human health?